BUILDING POSITIVE GROUP DYNAMICS IN ENGLISH LANGUAGE TEACHING AT TECHNICAL UNIVERSITY - Evstropova, Nina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
This paper is a report on the findings of a study conducted at Samara state technical university, at the faculty of engineering economics. The research is devoted to building positive group dynamics and interactive methods in ELT that are used to provide a positive group atmosphere. The author considers various interpretations of the concept “interactive methods”, analyses their effectiveness and develops a specific system of foreign language teaching that is focused on the participation of all students in the speech process and chooses “team-building technology” as a core element of this system and as a type of interactive methods that include complex of games in English. The results of the study prove that implementation of such games efficiently improves language level and builds a positive group dynamics.